Motivación y logros de aprendizaje en el área historia, geografía y economía en estudiantes de 3° de secundaria institución educativa Teniente Manuel Clavero Muga, Iquitos 2018 - Chota Braiz, Alexis Ivan (2021)
The objective of this research was: to know the level of motivation and learning achievements in the area of history, geography and economics in 3° grade students. High school degree - Educational Institution: Manuel Clavero Muga, Iquitos 2018. According to the scope of the research, it was correlational because it measured the degree of association between the variables: Motivation and Learning Achievements The general design of the research was non-experimental and the specific design was correlational transectional. The population and the sample were determined by the total number of students enrolled in the 3rd grade of secondary school of the educational institution Teniente Manuel Clavero Muga in the city of Iquitos in 2018, which was 142 students of different sexes. Data collection techniques was the survey for both variables. Independent: Motivation and it will be observed indirectly with the dependent variable: learning achievement. In conclusion, the study shows that there is a statistically significant relationship between motivation and learning achievement in 3rd year Secondary students, History, Geography and Economics area, at the Institution “Teniente Manuel Clavero Muga, Iquitos 2018, (P- value = 0.717> ? = 0.05).